2019
DOI: 10.1177/0969733019845136
|View full text |Cite
|
Sign up to set email alerts
|

Conscientious object in nursing: Regulations and practice in two European countries

Abstract: Background: The concept of conscientious objection is well described; however, because of its nature, little is known about real experiences of nursing professionals who apply objections in their practice. Extended roles in nursing indicate that clinical and value-based dilemmas are becoming increasingly common. In addition, the migration trends of the nursing workforce have increased the need for the mutual understanding of culturally based assumptions on aspects of health care delivery. Aim: To present (a) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 63 publications
0
28
0
3
Order By: Relevance
“…In the initial years of the course, the student is instrumentalized through theoretical classes, simulated practices and clinical practices and there is no clear definition of the hours that should be allocated to this type of education (5) . What has been observed in the state of to influencing students' confidence, their sense of belonging and respect for the user (4,16) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the initial years of the course, the student is instrumentalized through theoretical classes, simulated practices and clinical practices and there is no clear definition of the hours that should be allocated to this type of education (5) . What has been observed in the state of to influencing students' confidence, their sense of belonging and respect for the user (4,16) .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the hours of nursing courses developed in Europe, it is observed that, although there is a diversity of curricula, in most of the higher nursing schools, the student, in order to complete the first training cycle (degree), takes three to four years of formal education, and the minimum hours must not be less than 4,600 hours. It should be noted that 50% of this hours should be devoted to clinical teaching, that is, clinical practice in health units (4,(15)(16) , more than double the ECS hours required in Brazil (5) . However, the offer of clinical practices is also a challenge for the European countries, because the number of hours devoted to the clinical practice has varied between 30 and 60% of the total course load, showing the non-compliance with European legislation (16) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a general practice and policy, it is also found to be pertinent as one of the basic aspects of freedom in a democratic society. 13 Similar to the United States, the issue of conscientious objection is widely debated in Europe, and many individual practitioners have strong beliefs both for and against a provider's or pharmacist's right to use conscientious objection when it comes to dispensing emergency contraception. One study conducted with Norwegian medical students found that most of the support for conserving the right to use conscientious objection was in regard to the abortion procedure, not in regard to dispensing emergency contraception.…”
Section: United States Versus Europementioning
confidence: 99%